Pengaruh Rasio Likuiditas dan Rasio Aktivitas terhadap Pertumbuhan Laba Di RS Lng Badak Saat Pandemi dan Setelah Pandemi Covid 19 - Mustari, Mustari; Mahesa, Arjuna; Johansyah, Wahyu (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to analyze the influence of liquidity ratios and activity ratios on profit growth at RS LNG Badak, both during and after the COVID-19 pandemic. The study utilizes financial data from RS LNG Badak during the pandemic period and beyond. The analytical method employed is multiple linear regression to test the relationship between these variables. The research findings indicate that liquidity ratios and activity ratios have a significant impact on profit growth, both during and after the pandemic. However, the impact of the COVID-19 pandemic shows changes in the relationship between these ratios and profit growth. This study provides valuable contributions to understanding the financial performance of RS LNG Badak in facing the challenges posed by the pandemic. The results of the research show that liquidity ratios have a significant influence on profit growth at RS LNG Badak, with higher liquidity tending to contribute positively to profit growth. On the other hand, activity ratios also affect profit growth, with higher operational efficiency being associated with better profit growth. However, the impact of activity ratios on profit growth may differ during and after the Covid-19 pandemic, given changes in operational dynamics and patient demand. Keywords: Liquidity Ratios, Activity Ratios, Profit Growth.